I wear the black hat : grappling with villains (real and imagined) - Klosterman, Chuck, 1972- (Scribner, 2013)
The cultural critic questions how modern people understand the concept of villainy, describing how his youthful idealism gave way to an adult sympathy with notorious cultural figures to offer insight into the appeal of anti-heroes.